Caesarean section in Palestine using the Robson Ten Group Classification System: a population-based birth cohort study. Issue 10 (24th October 2018) - Zimmo, Mohammed Walid; Laine, Katariina; Hassan, Sahar; Bottcher, Bettina; Fosse, Erik; Ali-Masri, Hadil; Zimmo, Kaled; Sørum Falk, Ragnhild; Lieng, Marit; Vikanes, Åse
Abstract : Objective: To analyse the current situation of caesarean section in Palestine using the Robson Ten Group Classification System (TGCS). Design: A population-based birth cohort study. Setting: Obstetrical departments in three governmental hospitals in Gaza. Participants: All women (18 908) who gave birth between 1 January 2016 and 30 April 2017. Methods: The contributions of each group to the study population and to the overall rate of caesarean section were calculated, as well as the rate of caesarean section in each TGCS group. Differences in proportions between study hospitals were assessed by χ 2 test. Main outcome measures: The main outcome was the contributions of each group to the overall caesarean section rate. Results: The overall rate of caesarean section was 22.9% (4337 of 18 908), ranging from 20.6% in hospital 1 to 24.6% in hospital 3. The largest contributors to the overall caesarean section rate were multiparous women with single cephalic full-term pregnancy who had undergone at least one caesarean section (group 5, 42.6%), women with multiple pregnancies (group 8, 11.6%) and those with single cephalic preterm labour (group 10, 8.1%). Statistically significant differences in caesarean section rates between the study hospitals were observed in group 1 (nulliparous women with single cephalic full-term pregnancy and spontaneous labour), group 4 (multiparous with single cephalic full-term pregnancy with induced labour or prelabour caesarean section), group 5 (multiparous with single cephalic full-term pregnancy with previous caesarean section) and in group 7 (multiparous with breech presentation). Conclusion: Women in groups 5, 8 and 10 were the largest contributors to the overall caesarean section rate in the study hospitals. Efforts to reduce the differences in obstetrical care between hospitals need to be directed towards increasing the proportion of vaginal births after caesarean section and by reducing primary caesarean section in multiple pregnancies and preterm labour.